Association between birth weight and adolescent systolic blood pressure in a caucasian birth cohort differs according to skin type, CRH promoter or 11β-HSD2 genotype. Issue 9 (2nd May 2008) - Dwyer, T; Blizzard, L; Patterson, B; Ponsonby, A-L; Martin, K; Quinn, S; Sale, M M; Richards, S M; Morley, R; Rich, S; Dickinson, J L
Abstract : Objective: To examine whether the inverse association between birth weight and blood pressure varies by skin pigmentation and/or related genotypes. Study design: 671 children from a predominantly caucasian birth cohort were followed-up to adolescence (mean (SD) age 14.4 (0.64)). Methods: Data on birth weight, socioeconomic status, maternal antenatal smoking, adolescent blood pressure and polymorphisms of candidate genes were obtained and analysed by multiple linear regression. Results: An increase in birth weight of 1 kg was associated with an non-significant difference in adolescent systolic blood pressure of –0.53 mm Hg (95% CI –1.72 to 0.66) per kg after adjustment for child age and cohort entry criteria. The inverse association between birth weight and systolic blood pressure was stronger for those with darker skin (⩾2% melanin) (difference in effect, p = 0.02), those with more copies of the C allele of corticotropin-releasing hormone (CRH) +T1273C (p = 0.06), and those with more copies of the short (⩽236 bp) form of the 11β-HSD2CAnrepeat microsatellite (p = 0.03). Conclusions: These findings add to the evidence that cortisol-related pathways may account for at least part of the observed birth weight–blood pressure associations.